Pengaruh Tingkat Pendidikan, Pengalaman Kerja dan Gaya Kepemimpinan pada Efektivitas SPI Bank X Denpasar - Gimbara, Gintar; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 30 No 8 (2020)DO - 10.24843/EJA.2020.v30.i08.p13, 2020)
The purpose of this study was to determine the effect of education level, work experience and leadership style on the effectiveness of the internal control system. This research was conducted at Bank X Denpasar City. The number of samples taken was 35 employees, with saturated sample technique. Data collection is done by distributing questionnaires. The analysis technique used is multiple linear regression. The results of this study indicate that the level of education, work experience and leadership style partially have a positive effect on the effectiveness of the Bank X Denpasar internal control system. Supervision of the internal control system is important to have a high level of education in order to increase the ability to conduct supervision in an effort to increase the effectiveness of the internal control system. Keywords: Level of education; Work experience; Leadership Style; Effectiveness of the Internal Control System.